Postoperative ileocolic intussusception 48 hours after congenital heart surgery in an infant: a case report - Li, Huan; Ke, Mengyu; Yang, Jun (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPostoperative intussusception (PI) is a rare but potentially serious complication following congenital heart surgery in infants, often misdiagnosed due to its atypical presentation.Case presentationA 3-month-old male infant underwent aortoplasty, ventricular septal defect (VSD) repair, and patent ductus arteriosus (PDA) ligation for congenital heart disease. Approximately 72 h postoperatively, he developed bloody, jam-like stools. Emergency abdominal ultrasound, the first-line imaging modality, revealed ileocolic intussusception. Three attempts at ultrasound-guided hydrostatic saline enema reduction (pressure: 80 cm H2O) were unsuccessful, necessitating surgical exploration. Laparotomy identified an 8 cm ileocolic intussusceptum and a 10 cm ischemic ileal segment without a pathological lead point. The necrotic bowel was resected, and an end-to-end anastomosis was performed. The patient recovered uneventfully, was discharged three weeks postoperatively, and demonstrated normal growth at 6-month follow-up.ConclusionPrompt identification of postoperative intussusception—a rare complication following non-abdominal surgeries like congenital heart disease repair in infants—is of critical importance.